Creative approaches to improving participation : giving learners a say - Manchester, Helen (London : Routledge, 2012)
'Introducing creativity into the classroom is a challenge for governments and teachers. Employers around the world are increasingly interested in people who can think and work in a creative fashion. Families and Communities need people who are self-reliant, able to takes risks, to express and speak up for themselves and to be able to act independently. In recent years there has been a drive to make experiences at school more exciting, relevant, challenging and dynamic for all young people. Creative Approaches to Learning explores imaginative and creative ways to involve young people and children as stakeholders in their education. It looks at how they have actively participated in their own learning; transforming classrooms, curricula, school environments and teaching practices. Promoting reflection on current'student-teacher-school' relationships, links between home and school and between school and the wider world, the contributions within this book illustrate how the active engagement of students can lead to greater confidence, self-reliance and risk-taking; skills essential for a successful post-school career. Through an exploration of students' current inclusion in school life, this book provides: - A study of key issues and debates surrounding student participation - Ideas for increasing student participation and motivation for learning - Case studies from a range of creative learning projects with analysis of their achievements and challenges - Guidance on the creation of active, relevant and effective pedagogies - Practical suggestions for reflective practice and CPD A functional, accessible guide to creatively increasing students' participation'-- Provided by publisher.
Keywords: Student-centered learning; Active learning; Creative teaching; Motivation in education